Woodcarving motif and significance in the Malay house of Perak - Abdul Halim Choo, Iryani; Jamaludin, Nazrul Helmy; Rashid, Sabrizaa (Universiti Teknologi MARA, Perak, 2025)
Woodcarving motifs in traditional Malay houses transcend mere ornamentation, serving as cultural signifiers that express identity, belief systems, and a deep connection with the natural environment. In Perak, the Rumah Limas Bumbung Perak (RLBP) exemplifies this tradition through intricately carved fascia boards, wall panels, ventilation screens, and door heads. This study examines the typology, symbolism, and cultural significance of these motifs through qualitative field research on six RLBP case studies selected for their authenticity and preservation of original carvings, using non-intrusive observation, high-resolution photography, and scaled drawings. Findings show that floral and lattice motifs dominate, often arranged in Awan Larat compositions that combine aesthetic refinement with symbolic meaning rooted in Islamic philosophy and Malay cultural values. The absence of figurative motifs reflects adherence to Islamic artistic principles, while the prominence of floral forms underscores the community’s reliance on and reverence for nature. Motifs are deliberately selected to convey auspiciousness, social standing, and spiritual reminders, linking craftsmanship to intangible cultural narratives. This study contributes to the body of knowledge by documenting and analysing a lesser-studied regional variation of Malay woodcarving, offering valuable reference material for heritage conservation, restoration projects, and the sustainable integration of traditional motifs into contemporary architecture.